2016
DOI: 10.1093/hmg/ddv494
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of genome-wide association studies identifies multiple lung cancer susceptibility loci in never-smoking Asian women

Abstract: Genome-wide association studies (GWAS) of lung cancer in Asian never-smoking women have previously identified six susceptibility loci associated with lung cancer risk. To further discover new susceptibility loci, we imputed data from four GWAS of Asian non-smoking female lung cancer (6877 cases and 6277 controls) using the 1000 Genomes Project (Phase 1 Release 3) data as the reference and genotyped additional samples (5878 cases and 7046 controls) for possible replication. In our meta-analysis, three new loci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…FOXP proteins play key roles in cell cycle regulation and oncogenesis. Furthermore, meta-analysis, including those of studies in Japan and five other Asian countries, revealed that the FOXP4 SNP, rs7741164, is associated with a higher risk of lung cancer risk among never-smoking Asian females 22 , consistent with the aetiology of EGFR mutation-positive LADC 4 . Levels of FOXP4 mRNA expression in 403 non-cancerous lung tissues, as determined by real-time quantitative PCR, differed according to the rs2495239 SNP ( P by the linear regression test=0.023) genotype, suggesting high expression from the risk (A) allele ( Supplementary Table 15 ).…”
Section: Resultsmentioning
confidence: 92%
“…FOXP proteins play key roles in cell cycle regulation and oncogenesis. Furthermore, meta-analysis, including those of studies in Japan and five other Asian countries, revealed that the FOXP4 SNP, rs7741164, is associated with a higher risk of lung cancer risk among never-smoking Asian females 22 , consistent with the aetiology of EGFR mutation-positive LADC 4 . Levels of FOXP4 mRNA expression in 403 non-cancerous lung tissues, as determined by real-time quantitative PCR, differed according to the rs2495239 SNP ( P by the linear regression test=0.023) genotype, suggesting high expression from the risk (A) allele ( Supplementary Table 15 ).…”
Section: Resultsmentioning
confidence: 92%
“…2,3 Single nucleotide polymorphisms (SNPs) are the most common genetic variants that are found to be associated with cancer risk, including lung cancer. 4,5 Although genome-wide association studies (GWASs) have identified multiple SNPs to be associated with lung cancer risk, most of these SNPs have no annotated biological functions. 6,7 Therefore, we sought to perform a hypothesis-driven pathway-based analysis to identify possible functional SNPs that may be associated with lung cancer risk but have not been reported by previous single GWAS analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer susceptibility loci have been identified in Asian never-smoking females, which are distinct from those identified in smokers of European ancestry, suggesting that the genetic susceptibility and etiology of lung cancer could differ between groups of distinct ancestral origin and more importantly by smoking status. [13][14][15] Comprehensive tobacco control programs are helping to decrease the incidence of lung cancer in smoking men. However, the oncogenic process seems to differ among nonsmoking females.…”
Section: Smoking and Lung Cancer In Asiamentioning
confidence: 99%